Neonatal Tetanus - H. Tjandra; M. Munir (Indonesian Pediatric Society, 1978)
Analysis of 108 cases of Neonatal Tetanus by using a scoring system (Tjandra et al., 1974) revealed that 18 patients belonged to Grade I with a mortality rate of 5.6%; 43 belonged to Grade II with a mortality nate of 58.1%; and 47 belonged to Grade III with 91.5% mortality. The differences of mortality between the 3 groups are statistically significant. Mortality rate of 1973 was the lowest (50%) compared to that of 1972 (75%); 1974 (72.2%) and 1975 (61.4%). However, the number of patients belonging to Grade I in 1973 was the highest, 36.4%; whereas that of 1972 was 16.7%; 1974 was 11.1% and 1975 was 9.1 %. Classification of severity in Neonatal Tetanus is therefore, not only important for selecting a